5.25.3 Problems 201 to 300

Table 5.1103: Second order, Linear, Homogeneous and constant coefficients

#

ODE

Mathematica

Maple

2558

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

2559

\[ {}4 y^{\prime \prime }-y^{\prime }+y = 0 \]

2560

\[ {}y^{\prime \prime }+y^{\prime }+2 y = 0 \]

2561

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

2562

\[ {}2 y^{\prime \prime }-y^{\prime }+3 y = 0 \]

2563

\[ {}3 y^{\prime \prime }-2 y^{\prime }+4 y = 0 \]

2564

\[ {}y^{\prime \prime }+w^{2} y = 0 \]

2567

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

2568

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

2569

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

2570

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

2571

\[ {}6 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

2572

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

2835

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2836

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2837

\[ {}y^{\prime \prime }-\lambda y = 0 \]

2838

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2839

\[ {}y^{\prime \prime }-2 y^{\prime }+\left (\lambda +1\right ) y = 0 \]

2840

\[ {}y^{\prime \prime }+\lambda y = 0 \]

3059

\[ {}y^{\prime \prime }-4 y = 0 \]

3060

\[ {}y^{\prime \prime }+7 y^{\prime }+12 y = 0 \]

3061

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

3062

\[ {}y^{\prime \prime }-7 y^{\prime }+6 y = 0 \]

3063

\[ {}2 y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

3064

\[ {}y^{\prime \prime }-2 y^{\prime }-y = 0 \]

3065

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

3066

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

3067

\[ {}2 y^{\prime \prime }+2 y^{\prime }-y = 0 \]

3088

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

3089

\[ {}y^{\prime \prime } = 0 \]

3100

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = 0 \]

3245

\[ {}y^{\prime \prime } = k^{2} y \]

3246

\[ {}x^{\prime \prime }+k^{2} x = 0 \]

3266

\[ {}y^{\prime \prime } = y \]

3282

\[ {}x^{\prime \prime }-k^{2} x = 0 \]

3485

\[ {}f^{\prime \prime }+2 f^{\prime }+5 f = 0 \]

3558

\[ {}y^{\prime \prime }-25 y = 0 \]

3559

\[ {}y^{\prime \prime }+4 y = 0 \]

3560

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

3563

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

3564

\[ {}y^{\prime \prime }-9 y = 0 \]

3570

\[ {}y^{\prime \prime }-\left (a +b \right ) y^{\prime }+y a b = 0 \]

3571

\[ {}y^{\prime \prime }-2 a y^{\prime }+a^{2} y = 0 \]

3572

\[ {}y^{\prime \prime }-2 a y^{\prime }+\left (a^{2}+b^{2}\right ) y = 0 \]

3573

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 0 \]

3574

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

3590

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

3696

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 0 \]

3697

\[ {}y^{\prime \prime }+7 y^{\prime }+10 y = 0 \]

3698

\[ {}y^{\prime \prime }-36 y = 0 \]

3699

\[ {}y^{\prime \prime }+4 y^{\prime } = 0 \]

3935

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

3936

\[ {}y^{\prime \prime }+4 y = 0 \]

3955

\[ {}y^{\prime \prime }-y = 0 \]

4118

\[ {}y^{\prime \prime }+8 y^{\prime }+15 y = 0 \]

4119

\[ {}y^{\prime \prime }+2 y^{\prime }-15 y = 0 \]

4120

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

4121

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

4122

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

4123

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

4124

\[ {}2 y^{\prime \prime }+3 y^{\prime } = 0 \]

4125

\[ {}y^{\prime \prime }+25 y = 0 \]

4126

\[ {}4 y^{\prime \prime }+y^{\prime }+y = 0 \]

4127

\[ {}y^{\prime \prime } = 0 \]

4128

\[ {}y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

4161

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

4163

\[ {}25 y^{\prime \prime }-30 y^{\prime }+9 y = 0 \]

5916

\[ {}y^{\prime \prime }+2 y^{\prime } = 0 \]

5917

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

5918

\[ {}y^{\prime \prime }-y = 0 \]

5919

\[ {}6 y^{\prime \prime }-11 y^{\prime }+4 y = 0 \]

5920

\[ {}y^{\prime \prime }+2 y^{\prime }-y = 0 \]

5925

\[ {}y^{\prime \prime }-2 k y^{\prime }-2 y = 0 \]

5926

\[ {}y^{\prime \prime }+4 k y^{\prime }-12 k^{2} y = 0 \]

5928

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

5931

\[ {}y^{\prime \prime }-2 a y^{\prime }+a^{2} y = 0 \]

5937

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

5938

\[ {}y^{\prime \prime }-y^{\prime }+y = 0 \]

5940

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = 0 \]

5945

\[ {}y^{\prime \prime } = 0 \]

5946

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

5947

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

5948

\[ {}y^{\prime \prime }-4 y^{\prime }+20 y = 0 \]

6135

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

6136

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

6137

\[ {}y^{\prime \prime }+9 y^{\prime } = 0 \]

6138

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

6139

\[ {}y^{\prime \prime }-2 y^{\prime }+6 y = 0 \]

6140

\[ {}y^{\prime \prime }+16 y = 0 \]

6141

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

6142

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

6143

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

6144

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

6145

\[ {}y^{\prime \prime }+\left (1+2 i\right ) y^{\prime }+\left (-1+i\right ) y = 0 \]

6146

\[ {}y^{\prime \prime }+\left (1+2 i\right ) y^{\prime }+\left (-1+i\right ) y = 0 \]

6211

\[ {}r^{\prime \prime }-6 r^{\prime }+9 r = 0 \]

6243

\[ {}y^{\prime \prime } = -4 y \]

6245

\[ {}y^{\prime \prime } = y \]

6247

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

6388

\[ {}x^{\prime \prime }-\omega ^{2} x = 0 \]